'Frequently recurring' nocturnal polyuria is predictive of response to desmopressin in monosymptomatic nocturnal enuresis in childhood. Issue 2 (April 2019) - Marzuillo, P.; Marotta, R.; Guarino, S.; Fedele, M.C.; Palladino, F.; Capalbo, D.; Della Vecchia, N.; Miraglia del Giudice, E.; Polito, C.; La Manna, A.
Summary: Introduction: The nocturnal polyuria is considered a significant predictive value for response to desmopressin. The cutoff value useful to define nocturnal polyuria is still a matter of debate. Moreover, it is current notion that maximal voided volume (MVV) could be used as a predictor for desmopressin response. Objective: The objective of this study was to assess the impact of different definitions of nocturnal polyuria (and of its frequency) and MVV in predicting the response to desmopressin. Study design: A total of 103 patients with frequent monosymptomatic nocturnal enuresis (≥4 wet nights/week) were enrolled. A bladder diary over a 4-day period was collected. The MVV was defined as the highest micturition volume detected at bladder diary. Nocturnal diuresis was measured in 5 wet nights. Then, patients were administered with 120 mcg of sublingual desmopressin. After 2 months, if there was no complete response, the dose was increased to 240 mcg. Nocturnal polyuria was defined as follows: 1.Definition 1: nocturnal urine production >130% of the expected bladder capacity (EBC). 2. Definition 2: >100% EBC. 3. Definition 3: > 20×(age + 9) mL. The primary outcome was 'response to desmopressin' after 3 months of treatment. Results: Fifty-three patients responded to desmopressin. Comparing the responses to desmopressin on the basis of the three definitions of nocturnal polyuria, no significant difference was found. There was no cutoff value of nocturnal polyuria expressed as %EBC useful in providing a significant receiver-operating characteristic (ROC) curve. The area under the ROC curve for MVV expressed as %EBC was 0.67 (95% confidence interval [CI], 0.54–0.80; p = 0.01). A MVV >103.1% of EBC had 78.8% (95% CI, 61.1–91.0) sensitivity and 47.5% (95% CI, 31.5–63.9) specificity for predicting response to desmopressin. Among the patients with nocturnal polyuria according to definition 1, a higher percentage of subjects with nocturnal polyuria in 4 out of 5 or 5 out of 5 nights responded to desmopressin, compared with other patients. Patients presenting with nocturnal polyuria according to definition 3 in 5 out of 5 nights showed a 100% of response to desmopressin. At multivariate analysis, the only significant odds ratio (OR) to respond to desmopressin was that of patients with nocturnal polyuria according to definition 1 in >3 nights (OR = 7.1, 95% CI, 1.3–40.3). Discussion and conclusions: The presence or absence of nocturnal polyuria—according to all three definitions—in at least one night was not effective in predicting the response to desmopressin. Predictors of desmopressin response were nocturnal polyuria in >3 out of 5 wet nights according to definition 1 and in 5 out of 5 wet nights according to definition 3. Summary Figure Response to desmopressin on the basis of the number of nights with nocturnal polyuria among the 5 wet nights in which the nocturnal diuresis had been measured.The 'p' showed in Summary Figure derives from the comparison between the percentages of response to desmopressin on the basis of the number of nights with nocturnal polyuria defined accordingly with the 3 definitions. Chi-squared test was used for this comparison. Definition 1: nocturnal urine production >130% of the EBC [1, 6]. Definition 2: nocturnal urine production >100% of the EBC [3]. Definition 3: nocturnal urine production > than 20 × (age + 9) in mL [7]. EBC, expected bladder capacity. Summary Figure